2022
DOI: 10.1007/s11135-022-01412-x
|View full text |Cite
|
Sign up to set email alerts
|

Does military expenditure crowd out health-care spending? Cross-country empirics

Abstract: The trade-off between military expenditure and public health spending has remained an unsettled empirical issue. This paper investigates whether military expenditure has crowded out public health spending in 116 countries (including a subsample of 87 non-OECD countries) over the period 2000–2017. Through our system generalized methods of moments (GMM) estimations, we find that military expenditure, whether it is measured on a per-capita basis or as a proportion of total government expenditure, has a positive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Contrarily, empirical investigations also established that the decision to target military activeness as opposed to improved human capital development has birthed evidence of a crowding-out effect between military and health expenditure Ali, 2011;Zhang et al, 2017;Fan et al, 2018;Grigorakis and Galyfianakis, 2022;Ikegami & Wang, 2022).…”
Section: Theoretical and Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, empirical investigations also established that the decision to target military activeness as opposed to improved human capital development has birthed evidence of a crowding-out effect between military and health expenditure Ali, 2011;Zhang et al, 2017;Fan et al, 2018;Grigorakis and Galyfianakis, 2022;Ikegami & Wang, 2022).…”
Section: Theoretical and Empirical Reviewmentioning
confidence: 99%
“…A recent study by Grigorakis and Galyfianakis (2022) also supported evidence of the crowding-out hypothesis between military expenditure and public health expenditure, as positive changes in the former led to an increase in out-of-pocket health expenditure. Also, Ikegami and Wang (2022) revealed that using the system GMM for a group of 116 countries, there is evidence that military expenditure crowds out public health spending.…”
Section: Theoretical and Empirical Reviewmentioning
confidence: 99%
“…Climate disasters are not under human control but are not completely beyond human reach. Much less of the money spent on war could have been spent on innovation, food, and the health system (Ikegami & Wang, 2022). The world's medical system is still lacking (Kaiman et al, 2014;Rahman et al, 2020), facing newer types of diseases and challenges and will face more in coming days (Cazzolla Gatti, 2021;Koumoundouros, 2022;Geddes, 2022).…”
Section: (J) Fears Of Nuclear War or Biological Weapons Are Not Entir...mentioning
confidence: 99%
“…Climate disasters are not under human control but are not completely beyond human reach. Much less of the money spent on war could have been spent on innovation, food, and the health system (Ikegami & Wang, 2022). The world's medical system is still lacking (Kaiman et al, 2014;Rahman et al, 2020), facing newer types of diseases and challenges and will face more in coming days (Cazzolla Gatti, 2021;Geddes, 2022;Koumoundouros, 2022).…”
Section: Present Health System Sustainability Challenges In Conflict ...mentioning
confidence: 99%